Experimental study on high-power all-fiber superfluorescent source operating near 980 nm. (30th May 2018) - Ren, Yankun; Cao, Jianqiu; Ying, Hanyuan; Chen, Heng; Pan, Zhiyong; Du, Shaojun; Chen, Jinbao
Abstract: A high-power all-fiber superfluorescent source operating near 980 nm is experimentally studied with the help of a large-core distributed side-coupled cladding-pumped Yb-doped fiber. By optimizing the active fiber length and the angle cleaving of the output fiber facet, a 10 W all-fiber superfluorescent source operating near 980 nm is demonstrated for the first time, to the best of our knowledge. An 11.4 W combined 980 nm ASE power is obtained with a 9.3% slope efficiency and an 18 dB suppression of the ASE around 1030 nm. The output spectrum spans 973 nm to 982 nm with the 3 dB bandwidth around 3.5 nm. A 10.5 W output power with 13.1% slope efficiency is also obtained by changing the length of the active fiber. The variations of the output power and spectrum with the active fiber length and pump power are also investigated in the experiment.